Rekonstruksi penyusunan laporan keuangan BUMDes berbasis SAK EMKM menggunakan excel for Accounting - Hidayati, Nur; Mudrifah, Mudrifah; Wicaksono, Agung Prasetyo Nugroho (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2024)
The majority of MSMEs have difficulty making financial reports, especially BUMDes. Therefore, this research aims to determine the suitability of BUMDes Barokah's financial records with SAK EMKM and the recording system that has been implemented from the start of establishing the business until now. This study used descriptive qualitative method. The types of data used are primary data and secondary data. The primary data is the results of interviews with the BUMDes treasurer and the secondary data consists of recordings, financial reports and proof of transactions. This data was obtained by means of interviews and documentation. The research results show that the financial reports produced by BUMDes Barokah are not in accordance with SAK EMKM and the financial records are still manual. Financial records only consist of cash income and expenditure, and present profit and loss reports, capital changes reports and balance sheets. The cause of this discrepancy is the BUMDes treasurer's lack of understanding regarding accounting and computerization. It is hoped that the reconstruction of financial reports based on excel for accounting can provide a correct picture of financial reports in accordance with SAK EMKM based on technology to the treasurer of BUMDes Barokah.